TRENDS IN THE DEVELOPMENT OF UNDERSTANDING AND PRACTICE OF SOCIAL RESPONSIBILITY OF BUSINESS IN KAZAKHSTANI BANKS - Boltayeva Aigerim; Boltayeva Aigerim; Olzhabayeva Raushan; Makhatova Adelina; Dossalyanov Damir (Academic Journal of Physical and Chemical Sciences, 2019)
The global financial crisis has actualized the problems of enterprises and has focused attention on the need to restore trust in banks through corporate social responsibility. In this regard, social responsibility in the modern world is perceived not only as a charity, but also as an effective activity that enhances the business reputation and capitalization of the banks. The article analyzes the results of conducted specialized studies that demonstrate the level of awareness of business entities in Kazakhstan about the social responsibility of business, as well as understanding the concept of social responsibility of business by various stakeholders. In the author’s opinion, in Kazakhstan it is necessary to improve the system of social responsibility of business, to develop an analytical tool for the effectiveness of its functioning, to determine the procedure for the preparation and audit of social reporting at the legislative level.